Uncertainty Reduction Strategies on Share in Jar Skincare’s Purchase Intention - Talitha Argyanti; Nia Ashton Destrity (Universitas Muhammadiyah Yogyakarta, 2023)
Share-in-jar skincare products come up with a relatively high level of uncertainty as sales are commonly only made online, thus making it impossible for consumers to ascertain the product’s quality and suitability. Indonesians, on the other hand, are said to have a low uncertainty avoidance, which tends to be more tolerant of uncertainty and is supposed to be less active in seeking information to reduce uncertainty. This study aims to analyse the effect of uncertainty reduction strategies on the purchase intention of share-in-jar skincare products on marketplaces and social networking sites (SNS) in Indonesia. This study used an explanatory quantitative approach with a survey method. It involved 395 Indonesian consumers who had searched for information about share-in-jar skincare products through marketplaces or SNS. The multiple linear regression analysis revealed that Indonesian consumers had a low level of uncertainty avoidance but actively sought information before purchasing products. The passive, active, and interactive strategies simultaneously affected the intention to buy share-in-jar skincare products, but the active strategy had no effect when tested partially. The passive strategy was the most influential uncertainty reduction strategy toward the purchase intention of share-in-jar skincare products.